Aquatic Park Dengan Pendekatan Arsitektur Rumah Godang Kuantan Singingi - Safika Fitri; Wahyu Hidayat; Gun Faisal (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Swimsuit in Indonesia has been known for a long time by the wider community. Kuantan Singingi Regency is a regency that runs along the Kuantan river. In Kuantan Singingi coaching forswimming athletes has been done by the government. This guidance was made due to the absence of a swimming sport facility in Kuantan Singingi with a competition standard. The lack of a standard pool sports venue is the background of the design Aquatic Park. The design of Aquatic Park consider the function of the building to the location in the Sport Center area Kuantan Singingi. This design takes the typology of Rumah Kuantan Singingi Godang which is one of Traditional Houses Kuantan Singingi to display the characteristics of Kuantan Singingi form of architecture of Godang House. The concept used in this design is movement. The results of the concept of design transformation applied to the mass form of buildings and building facades.Keywords: Aquatic Park, Godang House, Recreation, Swimming.